2013
DOI: 10.1136/bmjopen-2013-002566
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of syphilis among HIV-infected individuals in Addis Ababa, Ethiopia: a hospital-based cross-sectional study

Abstract: ObjectiveTo determine the prevalence of syphilis and its risk factors among people with HIV at a hospital in Ethiopia.DesignA hospital-based cross-sectional study.SettingThis study was conducted at one of the largest public hospitals in Addis Ababa , Ethiopia.ParticipantsA consecutive 306 HIV-positive patients were recruited prospectively from January to March 2010. For comparative purposes, 224 HIV-negative consecutive attendees at the voluntary counselling and testing centre in the same period were also incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
21
6
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 7 publications
11
21
6
1
Order By: Relevance
“…This finding was similar to a prevalence rate of 10.0% reported in a study done in Uganda by Mboowa et al (11). It was as well similar to finding from a an Ethiopian study where 30 (9.8%) out of 306 HIV positive patients were found to be positive for seropositive for T.pallidum (10). This study showed lower Seroprevalence as compared to study done in Ghana by Mamoojee where 45(14.8%) out of 284 HIV positive participants and higher than study done in Rwanda by Mutagoma 20 (4.8%) out 482 HIV positive participant.…”
Section: Discussionsupporting
confidence: 91%
“…This finding was similar to a prevalence rate of 10.0% reported in a study done in Uganda by Mboowa et al (11). It was as well similar to finding from a an Ethiopian study where 30 (9.8%) out of 306 HIV positive patients were found to be positive for seropositive for T.pallidum (10). This study showed lower Seroprevalence as compared to study done in Ghana by Mamoojee where 45(14.8%) out of 284 HIV positive participants and higher than study done in Rwanda by Mutagoma 20 (4.8%) out 482 HIV positive participant.…”
Section: Discussionsupporting
confidence: 91%
“…People who reported being married to one person were significantly more frequently seropositive for T.pallidum (56.3% versus 53.5% in the TPHA negative). This finding is similar to study results from Uganda (13) and Ethiopia (14), and may be because of concurrency of partners. Specifically, Kenyon et al reported that male partner concurrency in which men had an average of five concurrent partners was significantly associated with high prevalence of syphilis (15).…”
Section: Discussionsupporting
confidence: 91%
“…The finding was similar to a prevalence rate of 10.0% reported in a study done in Uganda (13) and. and another in Ethiopia where (9.8%) out of 306 HIV positive patients were found to be seropositive for T.pallidum (14).The Seroprevalence that we observed was lower than that found in Ghana(14.8% of 284 HIVinfected participants)and higher than a study done in Rwanda in which (4.8%) of 482 HIV-infected participants were syphilis seropositive .…”
Section: Discussioncontrasting
confidence: 87%
“…Coast Metropolis was 10%. This was higher compared to what was noted in Addis Ababa, with prevalence of 1.6% infection [19] and 5.3% syphilis prevalence among HIV positive patients in Iran [20]. The findings may imply syphilis infection could be among the most common opportunistic infections affecting the P. Asare-Bediako et al In addition, the infection was high among the youth ages between 20 -39 years.…”
Section: Discussionmentioning
confidence: 67%